2021
DOI: 10.1007/s11332-021-00742-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with sera from Water Polo athletes activates AMPKα and ACC proteins In HepG2 hepatoma cell line

Abstract: Purpose Physical activity and professional physical activity such as water polo (WP) sport, has numerous beneficial effects to fight metabolism-related disorders through several mechanisms, including the promotion of liver metabolic adaptations, and the modulation of cytokine production. The aim of this study was to investigate the effects of different types of physical activity on AMPKα and ACC, two proteins involved in liver metabolism; therefore, we treated the hepatoma cell line Hep G2 with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The reasons for this may be related to the fact that the effect of exercise on the insulin pathway acts directly on skeletal muscle rather than liver. In addition to that, large amount of researches have reported that exercise would mediate insulin signaling pathways throughout the activation of Adenosine 5‘-monophosphate (AMP)-activated protein kinase (AMPK)/acetyl-CoA carboxylase (ACC) [ 39 ]. These reasons may have contributed to the negative results of exercise on the protein expression and phosphorylation of IRS/PI3K/AKT in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this may be related to the fact that the effect of exercise on the insulin pathway acts directly on skeletal muscle rather than liver. In addition to that, large amount of researches have reported that exercise would mediate insulin signaling pathways throughout the activation of Adenosine 5‘-monophosphate (AMP)-activated protein kinase (AMPK)/acetyl-CoA carboxylase (ACC) [ 39 ]. These reasons may have contributed to the negative results of exercise on the protein expression and phosphorylation of IRS/PI3K/AKT in this study.…”
Section: Discussionmentioning
confidence: 99%